Difference in Geography Study Results of Students Teached by PBL (Problem Based Learning) and PjBL (Project Based Learning) - Sitohang, Ayu Lestari; Damanik, M Ridha Syafii (JPG (Jurnal Pendidikan Geografi), 2024)
The purpose of this study was to determine the significant differences in Geography learning outcomes of students taught by PBL (Problem Based Learning) model compared to PjBL (Project Based Learning). This research is a quasi-experimental research with Pretest Posttest Control Group design. The data collection method used tests that were analyzed by t-tests. This research was conducted in class XI IIS SMAN 10 Medan. The results showed that the learning outcomes of students through the PBL learning model were 83.529 ± 6.801, while the learning outcomes of students with the PjBL model were 82.794 ± 7.092. Although the learning outcomes obtained are different, but the statistical test results show there is no significant difference between the learning outcomes of students taught with PBL and PjBL models α = 0.05 where Ha is rejected while H0 is accepted.Keywords: Learning Outcomes, Problem Based Learning, Project Based Learning